Decoding Grade B Pancreatic Fistula: A Clinical and Economical Analysis and Subclassification Proposal. Issue 6 (June 2019) - Maggino, Laura; Malleo, Giuseppe; Bassi, Claudio; Allegrini, Valentina; McMillan, Matthew T.; Borin, Alex; Chen, Bofeng; Drebin, Jeffrey A.; Ecker, Brett L.; Fraker, Douglas L.; Lee, Major K.; Paiella, Salvatore; et al.
Abstract : Objective: The aim of this study was to describe characteristics and management approaches for grade B pancreatic fistula (B-POPF) and investigate whether it segregates into distinct subclasses. Background: The 2016 ISGPS refined definition of B-POPF is predicated on various postoperative management approaches, ranging from prolonged drainage to interventional procedures, but the spectrum of clinical severity within this entity is yet undefined. Methods: Pancreatectomies performed at 2 institutions from 2007 to 2016 were reviewed to identify B-POPFs and their treatment strategies. Subclassification of B-POPFs into 3 classes was modeled after the Fistula Accordion Severity Grading System (B1: prolonged drainage only; B2: pharmacologic management; B3: interventional procedures). Clinical and economic outcomes, unique from the ISGPS definition qualifiers, were analyzed across subclasses. Results: B-POPF developed in 320 of 1949 patients (16.4%), and commonly required antibiotics (70.3%), prolonged drainage (67.8%), and enteral/parenteral nutrition (54.7%). Percutaneous drainage occurred in 79 patients (24.7%), always in combination with other strategies. Management of B-POPFs was widely heterogeneous with a median of 2 approaches/patient (range 1 to 6) and 38 various strategy combinations used. Subclasses B1–3 comprised 19.1%, 52.2%, and 28.8% of B-POPFs, respectively, and were associated with progressively worse clinical and economic outcomes. These results were confirmed by multivariable analysis adjusted for clinical and operative factors. Notably, distribution of the B-POPF subclasses was influenced by institution and type of resection ( P < 0.001), while clinical/demographic predictors proved elusive. Conclusion: B-POPF is a heterogeneous entity, where 3 distinct subclasses with increasing clinical and economic burden can be identified. This classification framework has potential implications for accurate reporting, comparative research, and performance evaluation. Abstract : Supplemental Digital Content is available in the text